Transcranial Magnetic Stimulation for Treatment-Resistant Depression: An Interactive Self-Learning Module - Junao Wang; Brent Nelson (Association of American Medical Colleges, 2018)
Introduction The use of transcranial magnetic stimulation (TMS) has become increasingly prevalent in psychiatry. A growing body of literature supports its use with treatment-resistant depression (TRD), and this indication has gained FDA approval. However, new psychiatry residents often have little exposure to or understanding of TMS. Methods This animated, fully narrated, self-learning module (SLM) introduces learners to TMS and its use in TRD and can be completed within 30 minutes. The goal is for viewers to be proficient with the basic science, indications, contraindications, side effects, and treatment process for TMS in TRD. Self-assessment questions throughout the module highlight and reinforce key learning points falling under the educational objectives. Results This SLM was deployed with PGY 1-4 training residents at the University of Minnesota during the 2016-2017 academic year as part of a study aimed at improving TMS education within our residency program. Fourteen residents participated in the study and offered feedback on the SLM's efficacy using 5-point Likert-scale surveys. Prior to the SLM's completion, the percentage of participants who disagreed or strongly disagreed with having met individual educational objectives ranged from 64% to 86%. Following completion, the percentage who agreed or strongly agreed with having met individual objectives ranged from 79% to 93%. Discussion This SLM provides an introductory curriculum on TMS for TRD to medical students and psychiatry residents who otherwise might not be adequately exposed to this treatment modality. As institutions adopt TMS, the module can serve as a primer for trainees prior to hands-on experience with the technology.